Transient splenial lesion syndrome in bipolar-II disorder: a case report highlighting reversible brain changes during hypomanic episodes - Zhou, Jingyuan; Cao, Yuan; Deng, Gaoju; Fang, Jinbo; Qiu, Changjian (Frontiers in Psychiatry, 2023)
Background: Reversible splenial lesion syndrome (RESLES) is a rare neurological condition characterized by temporary abnormalities in the splenium of the corpus callosum, which has been reported in mental disorders. Previous studies on bipolar disorder (BD) primarily focused on aspects such as brain structure and function, neurochemical changes, and genetics. However, there have been no studies reporting the occurrence of this syndrome during hypomanic episodes and its disappearance during the remission phase in bipolar disorder type 2 (BD-II). Case presentation: We present a case report of a 30-year-old female patient with BD-II who exhibited symptoms of RESLES during a hypomanic episode. The patient, with a 12-year psychiatric history, has experienced recurrent depressive episodes initially, with the first hypomanic episode occurring 8 years ago. During this period, this patient made several visits to the outpatient clinic to have her medications adjusted due to repeated suicide attempts. This time, she was admitted to our hospital with a second hypomanic episode due to drug withdrawal during pregnancy. The RESLES was observed on her brain magnetic resonance image, and it was alleviated after treatment with lithium carbonate and quetiapine until achieving remission. Conclusions: We present the first report of identifying RESLES in BD-II with hypomanic episodes, which subsequently disappears during the remission phase. Our case report highlights a potential association between BD and RESLES, emphasizing the need for future studies to explore the underlying mechanisms connecting these two conditions in greater depth.